Speciation evolution of zinc and copper during pyrolysis and hydrothermal carbonization treatments of sewage sludges. (1st April 2018) - Huang, Rixiang; Zhang, Bei; Saad, Emily M.; Ingall, Ellery D.; Tang, Yuanzhi
Abstract: Thermal and hydrothermal treatments are promising techniques for sewage sludge management that can potentially facilitate safe waste disposal, energy recovery, and nutrient recovery/recycling. Content and speciation of heavy metals in the treatment products affect the potential environmental risks upon sludge disposal and/or application of the treatment products. Therefore, it is important to study the speciation transformation of heavy metals and the effects of treatment conditions. By combining synchrotron X-ray spectroscopy/microscopy analysis and sequential chemical extraction, this study systematically characterized the speciation of Zn and Cu in municipal sewage sludges and their chars derived from pyrolysis (a representative thermal treatment technique) and hydrothermal carbonization (HTC; a representative hydrothermal treatment technique). Spectroscopy analysis revealed enhanced sulfidation of Zn and Cu by anaerobic digestion and HTC treatments, as compared to desulfidation by pyrolysis. Overall, changes in the chemical speciation and matrix properties led to reduced mobility of Zn and Cu in the treatment products. These results provide insights into the reaction mechanisms during pyrolysis and HTC treatments of sludges and can help evaluate the environmental/health risks associated with the metals in the treatment products. Graphical abstract: Image 1 Highlights: Anaerobic digestion enhanced sulfidation of Zn and Cu. Pyrolysis induced desulfidzation of Zn and Cu. HTC transformed Cu-sulfides into Cu-Fe-sulfides, and has little effects on Zn. Mobility of Zn and Cu was reduced after pyrolysis and HTC.